The effect of using artificial intelligence applications in improving selective attention of students with learning disabilities in the primary stage - Alghamdi, Enas Attia; Alghamdi, Sahar Hamdan; Alfarani, Leena Ahmad (Journal of Educational and Psychological Sciences, 2023)
This paper aims to improve the selective attention skill of female students with learning difficulties in the primary stage by using artificial intelligence applications, where the case study method was used to observe the selective attention of the sample. There were (24) students with learning disabilities between the ages of 9 and 12 years old in a primary school in the city of Jeddah in the Kingdom of Saudi Arabia, where the audio and visual aspect of the skill of selective attention was measured for the sample, and the study was conducted on one experimental group using two tools: the observation card and cognitive testing And two artificial intelligence applications in individual sessions for each student. The results of this study indicate that the use of artificial intelligence applications has a significant impact in improving selective attention for students with learning difficulties, also indicate that there is no effect of using artificial intelligence applications in improving selective attention in the auditory aspect of the skill of selective attention on the observation card. The study recommended using artificial intelligence applications as supporting techniques for individual learning to improve selective attention among students with learning difficulties.
Keywords: artificial intelligence applications; selective attention; learning difficulties